2002
DOI: 10.1364/ao.41.002740
|View full text |Cite
|
Sign up to set email alerts
|

Inherent and apparent scattering properties of coated or uncoated spheres embedded in an absorbing host medium

Abstract: The conventional Lorenz-Mie formalism is extended to the case for a coated sphere embedded in an absorbing medium. The apparent and inherent scattering cross sections of a particle, derived from the far field and near field, respectively, are different if the host medium is absorptive. The effect of absorption within the host medium on the phase-matrix elements associated with polarization depends on the dielectric properties of the scattering particle. For the specific cases of a soot particle coated with a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 16 publications
1
60
0
Order By: Relevance
“…In several papers, which have considered spherical particles in absorbing medium [22][23][24][25][26][27] , two different kind of optical characteristics of particles have been analyzed: inherent properties calculated near the particle surface (in the near field) and the so-called apparent properties calculated at large distances from the particle (in the far field). Yang et al 26 showed that the apparent properties (and corresponding efficiency factors of absorption and scattering)…”
Section: Theoretical Description Of Radiative Properties Of a Weakly mentioning
confidence: 99%
“…In several papers, which have considered spherical particles in absorbing medium [22][23][24][25][26][27] , two different kind of optical characteristics of particles have been analyzed: inherent properties calculated near the particle surface (in the near field) and the so-called apparent properties calculated at large distances from the particle (in the far field). Yang et al 26 showed that the apparent properties (and corresponding efficiency factors of absorption and scattering)…”
Section: Theoretical Description Of Radiative Properties Of a Weakly mentioning
confidence: 99%
“…There have been several attempts through mutant selection and engineering genes encoding key amino acid biosynthesis pathway enzymes to increase free essential amino acids in crop plants (2), but with limited success (3). A promising strategy is the genetic engineering of genes encoding proteins with high nutritional value into food crops (1,(4)(5)(6). However, despite promises that genetically modified (GM) crops could make a significant contribution to achieving global food security, the new-generation GM varieties are primarily used for industrial crops, such as cotton and animal fodder (7), and few have been commercialized.…”
mentioning
confidence: 99%
“…The conventional Lorenz-Mie formalism has been extended to study the scattering properties of coated spheres (e.g., Kattawar and Hood 1976;Toon and Ackerman, 1981;Bohren and Huffman, 1983;Kaiser and Schweiger, 1993;Fuller 1993;Mishchenko et al 2000;Fuller and Mackowski 2000;Yang et al 2002). In the present study, the standard code DMiLay.f for Mie calculations for coated spheres from Warren Wiscombe (NASA Goddard Space Flight Center).…”
Section: Mie Codes For Coated Spheresmentioning
confidence: 99%
“…The effect of black carbon on the scattering and absorption of solar radiation by cloud droplets has been investigated for almost four decades (Danielson et al, 1969;Chylek et al, 1984Chylek et al, , 1996Chylek et al, , 2000Twohy et al, 1989;Macke, 2000;Liu et al, 2002). Soot, either as an external attachment or as an internal inclusion, changes the refractive index of ice particles (Chylek and Hallett, 1992;Macke et al, 1996;Kuhn et al, 1998;Yang et al, 2002), and influences the scattering properties of ice particles, thereby altering the radiative forcing of ice clouds.…”
Section: Introductionmentioning
confidence: 99%